Circ-LRP6 Inhibits the Development and Progression of AAA Via miR-29a-3p/HIF-1α Axis - Wang, Fang; Sun, Zhijian; Yan, Wenke; Wang, Haiqing (Current Pharmaceutical Biotechnology, 2025)
BackgroundAt present, the research on the potential molecular mechanism of abdominal aortic aneurysm (AAA) is limited, which hinders the treatment of aneurysm and the development of drugs. CircRNA has been identified as a potential therapeutic target for diagnostic biomarkers in a variety of diseases. The purpose of this study was to explore the molecular mechanism of circLRP6 in AAA and to provide a theoretical basis for further clinical optimization of treatment.MethodsThe animal model and cell model of AAA were constructed, and the circLRP6 expression was verified by in situ hybridization and qRT-PCR. The effect of circLRP6 on cell viability was determined using CCK-8 and BrdU. The effects of circLRP6 on the cell cycle and apoptosis were determined by flow cytometry. In addition, the interaction of circLRP6 with miR-29a-3p and HIF-1α was verified by the luciferase reporter gene and RIP. HIF-1α or caspase 3 expression was detected by immunofluorescence or western blot analysis.ResultsOur previous results showed that the circLRP6 had reduced expression in AAA, and its overexpression significantly inhibited AngII-induced hAoSMC cell viability. In addition, bioinformatics prediction showed that there was a binding site between miR-29a-3p and circLRP6, showing a negative regulatory relationship in hAoSMC. In addition, the results of the luciferase reporter gene and RIP showed that the circLRP6 interacted with HIF-1α, and achieved effective treatment of AAA by inhibiting the miR-29a-3p/HIF-1α.ConclusionCircLRP6 effectively inhibited the development of AAA by inhibiting the miR-29a-3p/HIF-1α, providing a theoretical basis for further clinical optimization of treatment.
Keywords: progression